Quality Management, Ethics and Warfare – has rationality lost its rationale? - Part Two of Two - Lacerda-Nobre, Â.; Gameiro, A.; Duarte, R.; Pimentel, R. (XV Meeting of Quality Researchers | June 27, 2025, 2025)
not available yet